Pengaruh Kinerja Petugas Rekam Medis Terhadap Keakuratan Pengkodingan Fraktur - Julia Indriaty (Sekolah Tinggi Ilmu Kesehatan Sumber Waras, 2023)
Background: Accurate fracture coding is crucial in medical record systems as it affects patient data validity, insurance claims, and the planning and evaluation of healthcare services. The performance of medical record officers plays a crucial role in ensuring the accuracy of coding diagnoses and medical procedures. Objective: This study aims to analyze the impact of medical record officers' performance on the accuracy of fracture coding in hospitals. Methods: This study employs a quantitative approach with a cross-sectional design. Data were collected through direct observation, interviews, and analysis of medical records of patients diagnosed with fractures. Statistical tests were conducted to analyze the relationship between medical record officers' performance and the accuracy of fracture coding. Results: The study results indicate a significant relationship between the performance of medical record officers and the accuracy of fracture coding. Factors such as understanding of the disease classification system, meticulousness in documentation, and the level of experience of officers contribute to coding accuracy. Conclusion: The performance of medical record officers significantly influences the accuracy of fracture coding. Therefore, improving staff competence through training and periodic evaluations is essential to ensure optimal medical record data quality.